2002
DOI: 10.1074/jbc.m208588200
|View full text |Cite
|
Sign up to set email alerts
|

TFIIF-associating Carboxyl-terminal Domain Phosphatase Dephosphorylates Phosphoserines 2 and 5 of RNA Polymerase II

Abstract: The carboxyl-terminal domain (CTD) of the largest RNA polymerase (RNAP) II subunit undergoes reversible phosphorylation throughout the transcription cycle. The unphosphorylated form of RNAP II is referred to as IIA, whereas the hyperphosphorylated form is known as IIO. Phosphorylation occurs predominantly at serine 2 and serine 5 within the CTD heptapeptide repeat and has functional implications for RNAP II with respect to initiation, elongation, and transcription-coupled RNA processing. In an effort to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 57 publications
3
44
1
Order By: Relevance
“…By using this system, we observed that Fcp1 can dephosphorylate serine 5 but not serine 2 of the RNAPII CTD. This result was surprising, given that purified human Fcp1 has been shown previously to dephosphorylate these substrates with similar efficiency (50). Moreover, yeast FCP1 affects the serine 2 phosphorylation levels, whereas it has little, if any, effect on serine 5 phosphorylation levels in genes in vivo (17).…”
Section: Discussioncontrasting
confidence: 38%
“…By using this system, we observed that Fcp1 can dephosphorylate serine 5 but not serine 2 of the RNAPII CTD. This result was surprising, given that purified human Fcp1 has been shown previously to dephosphorylate these substrates with similar efficiency (50). Moreover, yeast FCP1 affects the serine 2 phosphorylation levels, whereas it has little, if any, effect on serine 5 phosphorylation levels in genes in vivo (17).…”
Section: Discussioncontrasting
confidence: 38%
“…First, phosphorylated and 32 Plabeled Pol II substrates were generated by in vitro phosphorylation using the Ser͞Thr kinase mitogen-activated protein kinase 2. Mitogen-activated protein kinase 2 phosphorylates Ser-2 and Ser-5 sites of the CTD in vitro as has been demonstrated by phosphorylated CTD-specific antibodies (43), although with preference toward Ser-5 (44). We confirmed conversion of Pol IIA to Pol IIO by a mobility change in the largest subunit (Rpb1) of Pol II in SDS͞PAGE (Fig.…”
Section: Yeast Fcp1 Phosphatase Activity Is Independent Of the Globularsupporting
confidence: 66%
“…In the present work, we show that full-length MINT enhances Runx2-dependent transcription, mediated via the autonomous Runx2 AD3. Consistent with a role in the activation of gene transcription, we demonstrate that MINT extensively co-localizes with RNAP IIo, the transcriptionally active and phosphorylated form of RNA polymerase (40).…”
Section: Discussionmentioning
confidence: 54%